(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Our judiciary believes in the principle that the innocent person must not be punished and at the same time, the guilty person must not be escaped. To punish the guilty person or to save the innocent person evidence plays an important role. The present era of technology has affected us in all the spheres of our life. Using DNA profiling as evidence is one of the best examples of how modern technology has transformed the justice delivery system. DNA contains general information common to all humans, so it is also known as the blueprint of life. two randomly selected individuals, from anywhere in the world, are supposed to be 99.9 percent genetically similar that is why the number of arms, legs, fingers, and toes remains exactly the same in all individuals but some parts of the stored information of DNA are unique and relate to only a specific person. On the basis of that unique information, offenders can be identified with the help of the DNA sample as well as innocents can easily be exonerated from suspects. In other words, DNA profiling is a very useful tool in the cases where we have to identify the perpetrator(s), the suspect(s), or victim(s) through the biological evidence traced from the body of the suspect(s), the victim(s), crime scene, or weapons used for committing the crime, etc. So, due to its utility, DNA Profiling has been getting increasing acceptance during the past thirty years and at present, it is extensively used by police, investigation agencies, prosecution, and defence advocates in courts across the globe. But in criminal cases, identity is not a major issue than mens rea or consent, for which ascertainment, DNA profiling is not helpful at all.